Music as care artistry in the hospital environment - Sarah Adams Hoover (CMS emerging fields in music, 2021)
This book provides an overview of professional musicians working within the healthcare system and explores programs that bring music into the environment of the hospital. Far from being onstage, musicians in the hospital provide musical engagement for patients and healthcare providers focused on life-and-death issues. Music in healthcare offers a new and growing area for musical careers, distinct from the field of music therapy in which music is engaged to advance defined clinical goals. Rather, this volume considers what happens when musicians interact with the clinical environment as artists, and how musical careers and artistic practices can develop through work in a hospital setting. It outlines the specialized skills and training required to navigate safely and effectively within the healthcare context. The contributors draw on their experiences with collaborations between the performing arts and medicine at Boston University/Boston Medical Center, University of Florida/UFHealth Shands Hospital, and the Peabody Institute/Johns Hopkins Medicine. These experiences, as well as the experiences of artists spotlighted throughout the volume, offer stories of thriving artistic practices and collaborations that outline a new field for tomorrow's musical artists